Approach to Limb Weakness - Bhagavan, Sachin M.; Ramaswamy, Swathi B.; Mehta, Tejas R.; Govindarajan, Raghav (Seminars in Neurology, 2021)
“Approach to limb weakness” provides an overview of the pathways of the motor system and the type of weakness seen with pathology at each level from the cortex to the muscle. This article provides the clinical pearls needed to identify different patterns of weakness and accurately localize the level of weakness. It offers important pointers that help distinguish among the different etiologies of weakness at each level, as well as various diagnostic approaches and treatments of diseases that lead to limb weakness. The diagnoses discussed are meant to be representative and not exhaustive, as a complete differential for each pattern of weakness is beyond the scope of this article.
Keywords: localization; patterns of weakness; upper motor; lower motor; limb weakness